Ketaatan Perizinan di Sektor Perdagangan Barang dan Jasa: Kesenjangan Implementasi dan Dampaknya terhadap Kepatuhan Pelaku Usaha - Yacob Ferdinan Martono; Rikardo Dinata; Yana Lestari; Nani Triwahyuni; Fadlilah Muntaha (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the importance of business licensing in the trade of goods and services sector as an instrument of legality, supervision, and legal protection; however, its implementation still faces gaps between normative regulations and practices in the field. The purpose of this study is to analyze the level of business actors’ compliance with licensing obligations, identify obstacles in the implementation of risk-based licensing policies, and evaluate their impact on compliance. The method used is library research with a normative juridical approach, through an examination of primary legal materials in the form of laws and related regulations, as well as secondary and tertiary legal materials from scientific literature. The results show that the effectiveness of risk-based licensing policies has not been optimally achieved due to low legal literacy, limited digital understanding, and the perception that licenses are merely a formality, causing many business actors to neglect administrative obligations. This condition illustrates the existence of a gap between regulatory objectives and implementation practices. These findings emphasize the need for procedural simplification, intensified socialization, and strengthened technical assistance so that licensing policies become more responsive to the needs of business actors, while simultaneously encouraging compliance and enhancing national economic competitiveness.